2011
DOI: 10.1371/journal.pone.0026828
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Share Research Data Is Related to the Strength of the Evidence and the Quality of Reporting of Statistical Results

Abstract: BackgroundThe widespread reluctance to share published research data is often hypothesized to be due to the authors' fear that reanalysis may expose errors in their work or may produce conclusions that contradict their own. However, these hypotheses have not previously been studied systematically.Methods and FindingsWe related the reluctance to share research data for reanalysis to 1148 statistically significant results reported in 49 papers published in two major psychology journals. We found the reluctance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
405
3
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(435 citation statements)
references
References 42 publications
18
405
3
9
Order By: Relevance
“…Estimates suggest that the majority of researchers do not adequately provide published data and materials, even when requested to do so by other researchers (Vanpaemel, Vermorgen, Deriemaecker, & Storms, 2015, 62%;Wicherts, Borsboom, Kats, & Molenaar, 2006, 73%). Though this lack of sharing may sometimes be due to purposeful withholding (see Wicherts, Bakker, & Molenaar, 2011), it is more likely that data and materials are simply stored improperly and lost (see Vines et al, 2014 (Deary et al, 2004). The old data have since been linked with current data, leading to dozens of new findings about how intelligence and other individual differences are associated with aging and long-term outcomes.…”
Section: Make It Available: Savementioning
confidence: 99%
“…Estimates suggest that the majority of researchers do not adequately provide published data and materials, even when requested to do so by other researchers (Vanpaemel, Vermorgen, Deriemaecker, & Storms, 2015, 62%;Wicherts, Borsboom, Kats, & Molenaar, 2006, 73%). Though this lack of sharing may sometimes be due to purposeful withholding (see Wicherts, Bakker, & Molenaar, 2011), it is more likely that data and materials are simply stored improperly and lost (see Vines et al, 2014 (Deary et al, 2004). The old data have since been linked with current data, leading to dozens of new findings about how intelligence and other individual differences are associated with aging and long-term outcomes.…”
Section: Make It Available: Savementioning
confidence: 99%
“…In 2015 Borgman identified four rationales for sharing research data: to reproduce research, to make those data that can be considered public assets, available to the public 4 , to leverage investments in research, and to advance research and innovation [18]. Several studies have furthermore reported that scientific papers accompanied by publicly available data are on average cited more often [19,20], and are moreover characterized by fewer statistical errors and a greater degree of robustness [21].…”
Section: Open Data: Sharing the Main Actor Of A Scientific Storymentioning
confidence: 99%
“…It is worth noting that this platform is not related to any specific journal or publisher, and as such constitutes a forum for public scientific discourse. Importantly, studies have shown that open peer-review can produce reviews of higher quality, with better verified claims, and more constructive criticisms, when compared to closed review [21,45]. Of course, one should keep in mind that open and transparent peer-review does not come without risks: especially young, early-career researchers might fear that by signing critical and thorough reviews they could become a target for retaliation at a sensitive point in their career.…”
Section: Open Peer-review: Transparent Research Evaluationmentioning
confidence: 99%
“…Sharing data is a natural in custom areas such as: astronomy and genomics [17]. Publishing the source data together with the research results, gives the proof of data good quality [18]. Authors of those publications choose their research to be publicly verified.…”
Section: The Analysis Of the Present Situationmentioning
confidence: 99%